A Process Model of Behavioral Problems in Elementary School Children: The Mediating Role of Child Emotion Management and the Moderating Role of Maternal Neuroticism in the Association Between Maternal Sense of Coherence and Child Behavioral Adjustment - Hosseini, Maryam Sadat; Khanzadeh Cherkhab, Mostafa; Goodarzi, Kourosh (Iranian Journal of Neurodevelopmental Disorders, 2027)
Purpose: The present study aimed to test a process model examining the mediating role of child emotion management in the relationship between maternal sense of coherence and behavioral problems among elementary school children, while considering the moderating role of maternal neuroticism.Methods and Materials: This study employed a descriptive-correlational design using a structural equation modeling approach. The statistical population consisted of elementary school students aged 7–12 years in Kermanshah during the 2024–2025 academic year, of whom 389 were selected through random multistage cluster sampling. Data were collected using Antonovsky’s Sense of Coherence Scale, the Achenbach Child Behavior Checklist, the Children’s Emotion Management Scales, and the Neuroticism dimension of the Five-Factor Personality Questionnaire. Data were analyzed using SPSS 26 and AMOS 26.Findings: The proposed model demonstrated an acceptable fit (χ²/df = 2.58, RMSEA = 0.064, CFI = 0.95). Maternal sense of coherence had significant direct negative effects on children’s maladaptive emotion management (β = −0.43, p < .001) and child behavioral problems (β = −0.16, p = .033), whereas maladaptive emotion management had a significant direct positive effect on behavioral problems (β = 0.65, p < .001). Moreover, the indirect effect of maternal sense of coherence on behavioral problems through child emotion management was significant (β = −0.28, p < .001). In addition, maternal neuroticism weakened the protective effect of sense of coherence.Conclusion: The findings indicated that maternal sense of coherence plays an important protective role in reducing behavioral problems by promoting children’s emotion management and that this pathway is influenced by maternal neuroticism. By simultaneously explaining the roles of maternal psychological resources, children’s emotional processes, and parental personality characteristics, the present findings provide evidence for designing family-centered interventions aimed at preventing and reducing behavioral problems in children.